VOCATIONAL GUIDANCE FOR STUDENTS AGED 15–18 (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This paper explores the importance and effectiveness of vocational guidance for students aged 15 to 18. During this critical developmental period, adolescents begin to form their identity and make important decisions about their future careers. The study highlights the psychological and pedagogical approaches that educators and counselors can utilize to help students discover their interests, abilities, and potential career paths. It also examines the role of family, educational institutions, and labor market trends in shaping students' career choices. The goal is to provide practical recommendations for developing and implementing career guidance programs that support informed and confident decision-making among high school students.